EFFICACY OF INTRACAMERAL MOXIFLOXACIN VERSUS TOPICAL MOXIFLOXACIN IN PREVENTING ACUTE ENDOPHTHALMITIS AFTER CATARACT SURGERY BY PHACOEMULSIFICATION - Anwar, Faisal; Nazia Qamar,; Asif Bashir,; Muhammad Tahir Ghaffar,; Mohammad Hasan Bokhari, (Journal of Ayub Medical College Abbottabad, 2024)
Background: Endophthalmitis is an acute infection of anterior and posterior segment of the eye involving aqueous humour and vitreous cavity along with the other structures. It is classified into many types including bacterial, Fungal, protozoal, viral and atypical forms. Most common route of infection is exogenous either after the surgery or traumatic perforation Objectives were of evaluate the efficacy of intracameral moxifloxacin versus topical moxifloxacin in preventing postoperative acute endophthalmitis after cataract surgery by phacoemulsification. Methods: Patients undergoing cataract surgery by phacoemulsification are divided into two groups. Group A and group B. Cataract surgery was performed by phacoemulsification in both the groups by the same consultant. Group A was given 0.5% intracameral moxifloxacin 0.1ml undiluted at the end of surgery and Group B received topical moxifloxacin eyedrops and no intracameral medicine at the end of surgery. Post-operative medicine in both the groups was same for 1st twenty-four hours that is topical dexamethasone 0.1%. Postoperative assessment was made on the next day or after twenty-four hours of surgery Our primary outcome was incidence of postoperative acute endophthalmitis. Results: The study comprised 150 eyes of patients. There were 75 patients in Group A (intracameral moxifloxacin) and 75 patients in Group B (Topical group). Mean age of the patients was 58 years . No case of endophthalmitis was reported in group A (intracameral moxifloxacin). Three cases in group A had acute toxic anterior segment with moderate corneal oedema and severe anterior chamber reaction which resolved in a week time without intravitreal medication. Group B (Topical Moxifloxacin) did not report any case of endophthalmitis. The difference between the two groups was very mild anterior chamber reaction in intracameral group as compared to topical group. Conclusion: 0.1 ml undiluted intracameral moxifloxacin 0.5% can be given as a last step in cataract surgery by phacoemulsification to prevent postoperative acute endophthalmitis infection. This drug administration is not totally safe as our three cases developed drug reaction with moderate corneal oedema and anterior chamber reaction that resolved in a week time.